2020
DOI: 10.1186/s41239-020-00223-0
|View full text |Cite
|
Sign up to set email alerts
|

Big data in education: a state of the art, limitations, and future research directions

Abstract: Big data is an essential aspect of innovation which has recently gained major attention from both academics and practitioners. Considering the importance of the education sector, the current tendency is moving towards examining the role of big data in this sector. So far, many studies have been conducted to comprehend the application of big data in different fields for various purposes. However, a comprehensive review is still lacking in big data in education. Thus, this study aims to conduct a systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 62 publications
(22 reference statements)
0
44
0
3
Order By: Relevance
“…On a higher level, the ability to find meaningful data and turn it into useable information by identifying patterns and deviations from patterns might be said to constitute BD's added value. According to [4], BD is now in a good position to begin tackling some of the major difficulties that HEd is currently experiencing. It could serve as the foundation for HEd to rethink both its financial model and the evidence used to make judgments about educational outcomes [2].…”
Section: Bd Analytics In Hedmentioning
confidence: 99%
See 3 more Smart Citations
“…On a higher level, the ability to find meaningful data and turn it into useable information by identifying patterns and deviations from patterns might be said to constitute BD's added value. According to [4], BD is now in a good position to begin tackling some of the major difficulties that HEd is currently experiencing. It could serve as the foundation for HEd to rethink both its financial model and the evidence used to make judgments about educational outcomes [2].…”
Section: Bd Analytics In Hedmentioning
confidence: 99%
“…[34] Stated that countries may take advantage of the numerous BD opportunities that are accessible to them in order to gain value from the huge volumes of data that are generated and, in the long term, aid in their development. BD and analytics in HEd have the potential to be transformative, affecting existing processes of administration, teaching, and learning, as well as contributing to policy outcomes by assisting in the resolution of existing difficulties facing educational institutions [4,35]. The following are some examples of how successful institutions have made use of BD.…”
Section: Proposed Framework Future Research and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, there has been various works being carried out towards analyzing such education data. Existing studies on big data is found to use sophisticated tools and framework [5][6][7][8]. However, such complex adoption cannot be taken into consideration in real cases.…”
Section: Introductionmentioning
confidence: 99%